Contemporary Sino-French cinemas. Absent fathers, banned books, and red balloons - Bloom, Michelle E. (Critical interventions., 2016)
Transnational cinemas are eclipsing national cinemas in the contemporary world, and Sino-French films exemplify this phenomenon through the cinematic coupling of the Sinophone and the Francophone, linking France not just with the Chinese mainland but also with the rest of the Chinese-speaking world. Sinophone directors most often reach out to French cinema by referencing and adapting it. They set their films in Paris and metropolitan France, cast French actors, and sometimes use French dialogue, even when the directors themselves don't understand it. They tend to view France as mysterious, sexy, and sophisticated, just as the French see China and Taiwan as exotic. As Michelle E. Bloom makes clear, many films move past a simplistic opposition between East and West and beyond Orientalist and Occidentalist cross-cultural interplay. Bloom focuses on films that have appeared since 2000 such as Tsai Ming-liang's What Time Is It There?, Hou Hsiao-hsien's Flight of the Red Balloon, and Dai Sijie's Balzac and the Little Chinese Seamstress. She views the work of these well-known directors through a Sino-French optic, applying the tropes of metissage (or biraciality), intertextuality, adaptation and remake, translation, and imitation to shed new light on their work.